Penggunaan probiotik Lactobacillus paracasei ssp paracasei M13 terenkapsulasi karagenan-skim pada pembuatan Yoghurt Jambu Biji (Yojabi) - Mutia Elida; Gusmalini Gusmalini; Iza Ayu Saufani (Unri Conference Series: Community Engagement, 2019)
Probiotic Lactobacillus paracasei ssp paracasei Ml3 encapsulated carrageenan-skim was applied in the making of guava yoghurt as a substitute for natural starter curd to produce yoghurt quality and beneficial for health. Yoghurt “yojabi” is one of the flagship products PPUPIK probiotics Politani Payakumbuh. The method of activity is direct demonstrating, training and mentoring production process in the production group PPUPIK. The starter encapsulated carrageenan-skim 2:1 in the form of a wet capsule was inoculated by 3% into pasteurized milk and then fermented for 12 hours. The next process is a homogenizer by added guava pasteurized fruit juices and then packing. The results are that use encapsulated starter in the form of wet capsules let capsules as a starter into the fermentation container. Total lactic acid yoghurt is 1.09%, pH 4.6, and total lactic acid bacteria 9,2 log CFU/ml, the water content of 75.84%, ash content of 0.69%, protein levels of 4%, fat content 3.08%, and total carbohydrate 16.39%. Financial analysis obtained R/C ratio 1.48, and price BEP 3.382,30.